Australia's News Media Bargaining Code and the global turn towards platform regulation - Bossio, Diana; Flew, Terry; Meese, James; Leaver, Tama; Barnet, Belinda (Wiley, 2022)
Governments across the world are struggling to address the market dominance of technology companies through increased regulation. The Australian Federal government found itself leading the world in platform regulation when, in 2021, it enacted the Australian News Media and Digital Platforms Mandatory Bargaining Code. The furore surrounding the introduction of the legislation, and Facebook's subsequent Australian ‘news ban’ exposed the limits of a regulatory model that has previously left the tech industry to moderate itself. In this paper, we argue the introduction of the Code is a leading example of a global trajectory towards regulatory change, which sees governments move from a reactive regulation model to specific interventions around the governance of digital media spaces. We discuss how best to measure the successes and failures around this more interventionist model through a case study of the implementation of the Code in Australia. More broadly we consider how global platforms have responded, and whether the reform is an effective regulatory model for other national governments to emulate.